Determinants of routine immunization coverage in Bungudu, Zamfara State, Northern Nigeria, May 2010 - Gidado, Saheed (The African Field Epidemiology Network, 2014)
INTRODUCTION: Immunization is a cost-effective public health intervention to reduce morbidity and mortality associated with infectious diseases. The Nigeria Demographic and Health Survey of 2008 indicated that only 5.4% of children aged 12-23 months in Bungudu, Zamfara State were fully immunized. We conducted this study to identify the determinants of routine immunization coverage in this community. METHODS: We conducted a cross-sectional study. We sampled 450 children aged 12-23 months. We interviewed mothers of these children using structured questionnaire to collect data on socio-demographic characteristics, knowledge on immunization, vaccination status of children and reasons for non-vaccination. We defined a fully immunized child as a child who had received one dose of BCG, three doses of oral polio vaccine, three doses of Diptheria-Pertusis-Tetanus vaccine and one dose of measles vaccine by 12 months of age. We performed bivariate analysis and logistic regression using Epi-info software. RESULTS: The mean age of mothers and children were 27 years (standard error (SE): 0.27 year) and 17 months (SE: 0.8 month) respectively. Seventy nine percent of mothers had no formal education while 84% did not possess satisfactory knowledge on immunization. Only 7.6% of children were fully immunized. Logistic regression showed that possessing satisfactory knowledge (Adjusted OR=18.4, 95% CI=3.6-94.7) and at least secondary education (Adjusted OR=3.6, 95% CI=1.2-10.6) were significantly correlated with full immunization. CONCLUSION: The major determinants of immunization coverage were maternal knowledge and educational status. Raising the level of maternal knowledge and increasing maternal literacy level are essential to improve immunization coverage in this community.